Ensayos de eficiencia con macrófitas para la remoción de carga contaminante en aguas residuales de hatos lecheros para un subsector de la Laguna Fúquene - Rodríguez R., Luís Francisco; Ortiz Muñoz, Yoldi Dalila; Navarro Chaparro, Hernando; Espinosa García, Helmut; Hernandez Montaña, Vilma (Revista Científica, 2006)
This research project was developed in two phases. In the fist phase the wastewater characterization was made in two milk´s production farms located in Susa (Cundinamarca), section of Funquene´s lagoon. The farm named ¨Las delicias¨ was determined as the most critical point; using their organic liquid residues to feed the wetlands system implemented in the second phase, in which the organic matter removal percentages and nutritious such as:BOD, COD, NO, POand total solids were evaluated using a pilot scale. The macrophytes specias used as base of the practice were Eichhornia crassipes (Buchón), Limnobium Laevigatum (Floating leaf) and Typha domingensis (Eneal), extracted of Fuquene´s lagoon. The statiscal analysis was made using a random simple block system and it shows that Eichhornia crassipes has a bigger efficiency in the organic load removal (65%) for these kind of liquid residues.